The diagnosis of inflammatory bowel disease is often unsupported in clinical practice. Issue 1 (January 2015) - Canavese, Gabriella; Villanacci, Vincenzo; Sapino, Anna; Rocca, Rodolfo; Daperno, Marco; Suriani, Renzo; Maletta, Francesca; Cassoni, Paola; the members of the Piedmont IBD group, 1
Abstract Background The diagnosis of inflammatory bowel disease can be challenging and requires the efforts of a multidisciplinary team. We performed a retrospective analysis with the aim of evaluating the adequacy of the prerequisites for arriving at an accurate histological diagnosis. Methods The following parameters were considered as prerequisites for a diagnosis of inflammatory bowel disease: clinical and endoscopic data; proper sampling and handling of biopsies; and elementary microscopic lesions. We collected 345 cases from 13 centres. Results The date of onset and treatment were available for 13% and 16% of the cases, respectively. Endoscopy information was accessible for 77% of the cases. Endoscopic mapping was completed in 13% of the cases. In no cases were the biopsies oriented on acetate strips. The diagnosis was conclusive in 47% of the cases. Activity, epithelial disruption and crypt distortion were described in 35% of the reports with a conclusive diagnosis. Conclusion Our study showed that the diagnostic prerequisites were widely unfulfilled, although approximately half of the diagnoses were conclusive for inflammatory bowel disease. Thus, in our assessment of clinical practice: (1) clinicians seldom provide suitable clinical and/or endoscopic information for a histological diagnosis and (2) histopathological diagnoses of inflammatory bowel disease are often not supported by morphology.